"Verd de proximitat BCN": Monitoring and evaluation plan for the operation and impact of green roofs and façades in the city of Barcelona. Issue 1 (1st December 2022) - Pérez Luque, Gabriel; Coma Arpon, Julià; Reyes Rogget, Marcelo; Marias Gonzalez, Gerard
Abstract: Among the multiple Nature-based solutions (NBS) that can be applied at city scale, those that make it possible the integration of vegetation and nature on the building's envelopes, such as green roofs, green walls and green facades, stand out for their ability to re-fill those scarce surfaces of opportunity in the dense built environment. The main objective of the " Verd de proximitat BCN " project is to design a "Monitoring and evaluation plan to assess the impact of green roofs and façades in the city of Barcelona", which must be inclusive and participatory, economically viable and sustainable over time. To this end, 4 ongoing real projects are being retrospectively monitored in order to evaluate their impact. With the obtained results, a proposal for the future "Monitoring and evaluation plan for the operation and impact of green roofs and façades" will be drafted to be applied in future projects during the design phase of these solutions (prospective monitoring).